2015
DOI: 10.1093/icb/icv080
|View full text |Cite
|
Sign up to set email alerts
|

Exoskeletons across the Pancrustacea: Comparative Morphology, Physiology, Biochemistry and Genetics

Abstract: The exoskeletons of pancrustaceans, as typified by decapod crustaceans and insects, demonstrate a high degree of similarity with respect to histology, ultrastructure, function, and composition. The cuticular envelope in insects and the outer epicuticle in crustaceans both serve as the primary barrier to permeability of the exoskeleton, preventing loss of water and ions to the external medium. Prior to and following ecdysis, there is a sequence of expression and synthesis of different proteins by the cuticular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 79 publications
1
47
0
1
Order By: Relevance
“…The increased expression of cuticular contigs after 7‐day exposure suggested that cyclic hypoxia might exert an effect on the moult cycle of P. varians , similarly to that reported for insect larvae reared in hypoxia (Kivelä et al., ). This conclusion was supported by the upregulation of PMP, CaAP and DD5 genes, markers highly expressed during postmoult phase in crustaceans (Ikeya et al., ; Inoue, ; Roer et al., ).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The increased expression of cuticular contigs after 7‐day exposure suggested that cyclic hypoxia might exert an effect on the moult cycle of P. varians , similarly to that reported for insect larvae reared in hypoxia (Kivelä et al., ). This conclusion was supported by the upregulation of PMP, CaAP and DD5 genes, markers highly expressed during postmoult phase in crustaceans (Ikeya et al., ; Inoue, ; Roer et al., ).…”
Section: Discussionmentioning
confidence: 88%
“…cuticular proteins, Supporting Information Table S4). Further, we identified proteins expressed in the postmoult phase of crustaceans and involved in deposition and calcification of the newly formed exoskeleton: postmoult protein ( PMP ), calcification‐associated peptide ( CaAP ), peptides DD5 and M28 (Ikeya, Persson, Kono, & Watanabe, ; Inoue, ; Roer et al., ). Among the downregulated transcripts, the majority were identified as chitinase enzymes (Abehsera et al., ) and a downregulation of a vitellogenin transcript was observed.…”
Section: Resultsmentioning
confidence: 99%
“…The exoskeleton of shrimp is composed of the polysaccharide chitin, cuticle proteins and mineral deposits. It is a four-layered matrix including an epicuticle, exocuticle, endocuticle and epidermis 20 . According to the appearance of the epidermis, pigmentation, the formation of new setae, and the presence of matrix or internal cones in the setal lumen, the moulting cycle of shrimp can be divided into four recurrent stages: inter-moult, pre-moult, the moment of the moulting behaviour/ecdysis and post-moult 2123 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The joints, gills, branchial chamber lining, foregut (including the gastric mill), and hindgut of the blue crab are all ectodermally derived tissue and thus, like the dorsal carapace, have cuticular layers (Johnson, ; Roer and Dillaman, ). Variations in structure (dimensions of cuticular layers, degree or absence of mineralization, type of mineral) and the timing of resorption and deposition have been documented in different cuticular regions (Andrews and Dillaman, ; Elliott and Dillaman, ; Roer et al, ). For example, in the crayfish Procambus clarkii , apolysis in the gill filaments occurs later than in the telson and general body surface.…”
Section: Introductionmentioning
confidence: 99%